Draft Genome Sequence of Pseudomonas putida CBF10-2, a Soil Isolate with Bioremediation Potential in Agricultural and Industrial Environmental Settings - Iyer, Rupa (Genome Announc, 2016)
Pseudomonas putida CBF10-2 is a microorganism isolated from farmland soil in Fairchild, TX, found to degrade high-impact xenobiotics, including organophosphate insecticides, petroleum hydrocarbons, and both monocyclic and polycyclic aromatics. The versatility of CBF10-2 makes it useful for multipurpose bioremediation of contaminated sites in agricultural and industrial environments.